The impact of open and closed mindsets on evaluative priming - Alexopoulos, Theodore; Fiedler, Klaus; Freytag, Peter (Cognition & emotion, 2012)
In the present research, we argue that open versus closed mindsets, accompanying ongoing versus completed mental jobs on the prime, determine the size of congruity effects in the evaluative priming paradigm. More specifically, we hypothesised that disfluent primes that resist an easily completed encoding process should induce an open mindset and thereby result in stronger congruity effects than fluent primes that induce closed mindsets. Across two experiments, we applied two different manipulations of prime fluency: gradual demasking (Experiment 1) and colour contrast (Experiment 2). As expected, in both experiments we found robust congruity effects, but only on trials with disfluent (vs. fluent) primes. Results of a follow-up experiment suggest that these effects are not due to attentional processes. We conclude that the mindsets resulting from individuals' activities during encoding are crucial in determining the outcome of evaluative priming effects.